Multimodality Imaging Evaluation in Coronary Artery Disease - Anna Fuji Rahimah (Heart Science Journal, 2022)
Non-invasive imaging modalities are fundamental in evaluating and managing patients with known or suspected coronary artery disease (CAD). Multimodality cardiac imaging procedures detect the presence of CAD and guide clinical decision-making. Combining anatomical and functional imaging modalities would enable a more thorough characterization of obstructive CAD. When selecting an imaging test, one must consider the many factors that interact in the development of chronic CAD and acute coronary syndrome (ACS). The clinical presentation, baseline characteristics of the patient, as well as the clinical center's local availability and expertise will determine the preferred imaging technique to confirm the diagnosis of ACS or chronic CAD. Diagnostic testing is most useful and recommended in patients with chronic coronary syndromes (CCS) when the likelihood is intermediate. The preferred options are coronary computed tomography angiography (CTA) or stress tests, but patients may be referred directly for invasive coronary angiography (ICA) if the likelihood of CAD is very high. The primary goal of the initial diagnostic evaluation in patients with suspected ACS is to confirm ACS and rule out the other most common life-threatening conditions, such as acute pulmonary embolism (PE) or acute aortic syndromes (AAS). Non-invasive imaging is essential in the differential diagnosis of ACS and frequently necessitates multimodality imaging. Cardiac magnetic resonance (CMR) is the most helpful imaging test in diagnosing myocardial infarction with non-obstructed coronary arteries (MINOCAs), and it can detect or rule out other cardiac causes of troponin rise.